Axiological Features of the Concept CHARM / CHARIVNIST in the English and Ukrainian Languages (Contrastive Aspect) - Yuliia Tomchakovska (Психолінгвістика, 2018)
The article is devoted to the study of the linguo-cultural concept CHARM / CHARIVNIST in the English and Ukrainian languages. The aim of the work is to identify axiological characteristics of the CHARM / CHARIVNIST concept in English and Ukrainian Internet discourses on the basis of the text-recommendations “How to be Charming” / “Yak staty charivnoyu”, etc. The object of the research is concept CHARM / CHARIVNIST as an aesthetic component of the English and Ukrainian world images; the subject – similarity, difference and contrast in the ways of verbalization of concept CHARM / CHARIVNIST in the English and Ukrainian languages and peculiarities of the discourse realization of the given concept in corresponding linguocultures. Internal and external characteristics of the formation of the image of the CHARMING PERSON have been singled out. Internal features are semantic indicators of the concept CHARM / CHARIVNIST. External features are physical indicators of the concept and include mimic, eye contact, voice and touching features. For English-speaking recipients, such axiological feature as SELF-DEVELOPMENT or DEVELOPMENT OF PERSONALITY is important, which is foregrounded through its components: self-esteem, self-confidence, self-control, “simply-be-yourself” that appear first of all in the body language, for example, FACE (satisfaction, expressive), SMILE (genuine, big, friendly, sincerely), EYE CONTACT (direct), TOUCHING (light), HANDSHAKE (firm), and VOICE (boldness, confident, gentle, peaceful, direct). The following axiological features of the concept of CHARIVNIST in the Ukrainian texts-recommendations have been singled out: sincerity, cheerfulness, originality, with physical characteristics (eyes, voice, smile) serving as "external indicators of the charming inner world", for example, eyes as a mirror of the soul, a smile as a generator of positive fluids, etc. It has been proved that the discoursive feature of SELF-DEVELOPMENT of the English concept CHARM is contrasting. It has been established that such discoursive feature of the Ukrainian concept CHARIVNIST as ORIGINALITY is contrasting, and the discoursive features CONFIDENCE and VPEVNENIST are integral to the two concepts.